(untitled) - Schneider, David C. (San Diego, 1994)
Quantitative Ecology reviews the manifold ways that scale influences the interpretation of ecological variation. Ecologists recognize the significance of scale and magnitude in providing a context for resolution of ecological problems. Written for advanced undergraduates, graduate students, and faculty researchers, this book synthesizes a burgeoning literature on the influences of scale.
Keywords: Ecology,Sinh thái học; Mathematics,Toán học